Budget model of Federal Universities: factors that motivates and inhibits its institutionalization - Reis, Cisne Zélia Teixeira; Oliveira, Adriel Rodrigues de; Silveira, Suely de Fátima Ramos; Cunha, Nina Rosa da Silveira (Revista de Administração da UFSM, 2018)
The budget allotment among federal universities is based on a mathematical model that considers the production and the academic performance of each institution in a set of variables, presenting as result the budget amount that each university is entitled. It is essential that university administrators know, follow and are structured in favor of the best results in the variables that follow this model. Investigating the university’s commitment to improve its management skills in support of effective incorporation of the budget model in its habits and routines can lead to discoveries and important contributions to the improvement of management. It has been appealed to the Institutional Theory, from the perspective of stages of Habitualization, Objectification and Sedimentation to identify motivators and inhibitors of the complete institutionalization of the model, the perception of the six managers of budget planning area that, in the period 2001-2011, occupied Forplad’s coordinators function and its Model Committee. Characterized as a descriptive research with a qualitative approach, the applied interviews were submitted to Content Analysis Technique. It can be concluded that the budget model is an instrument of great importance in the process of transparency and university public administration, however, it presents inhibiting factors to its best level of institutionalization in the three stages.